Efficacité d’utilisation de jeu cartes UNO pour améliorer la compétence de la production orale les élèves de SMK Telkom 2 Medan - Putri Namira, Indah; Adawi, Rabiah (Universitas Negeri Semarang, 2025)
This research aimed to determine the difference in speaking ability between the experimental class who took part in learning using the UNO card game application. This research also seeks to test the effectiveness of the UNO card game for learning numbers in French for students at SMK Telkom 2 Medan. This research uses a quantitative approach with experimental methods and a group pretest-posttest design. The data collection techniques used in this research were observation, tests, and interviews. Data is analyzed using quantitative data analysis techniques with the application SPSS. The average pretest score was 27 and became 78 in the posttest average score. The N-gain test is calculated to determine the efficiency of the UNO card game. The average student’s pre-test and post-test scores increased by 72% based on the results. Regarding the Media Effectiveness Test Chart, 72% fall into the effective category. It can be concluded that the UNO card game is efficacious in improving oral production skills in learning number material at SMK Telkom 2 Medan.